Gambaran Pengetahuan, Sikap, dan Tindakan Masyarakat dalam Mematuhi Protokol Kesehatan Setelah Menerima Vaksinasi Covid-19 di Dusun Gubug Tahun 2022 - Monica Sonya Novenda; Indrayanti Indrayanti (Journal of Health (JoH), 2023)
The government carries out a Covid-19 vaccination program to protect the people from the danger of Covid-19. Though, some people think after receiving Covid-19 vaccination there is no need to comply with health protocols because it is safe. The results of observation in Gubug revealed some people did not wear mask and keep their distance. The interview with five people showed three people did not comply with the health protocol after vaccination because they felt safe. This research aims to know community’s knowledge, attitude, and action in obeying health protocol after receiving Covid-19 vaccination at Gubug Village in 2022. This was quantitative descriptive method research. The sample was 95 respondents taken by simple random sampling technique. The instrument was questionnaire with 30 questions and used univariate analysis. Result it showed 83 people (87.4%) had a good knowledge, 78 people (82.1%) had good attitudes, 59 respondents (62.1%) had a sufficient action in complying with health protocols after vaccination. Conclusion is the people of Dusun Gubug had good knowledge and attitude also sufficient action in complying with health protocols after receiving Covid-19 vaccination in 2022.